2016
DOI: 10.2109/jcersj2.16148
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing stability of Co gradient in nano-structured WC–Co functionally graded composites using graphene additives

Abstract: A new approach for stabilizing a predesigned Co gradient in the microstructure of nano WCCo thinning structure via graphene additions is presented. For this purpose, laminated specimens of green WCCo functionally graded material, having three layers structured, with and without graphene additions in the intermediate layer were sintered at solid and liquid sintering temperatures of 1290 and 1400°C, respectively, using the hot isostatic pressing technique (HIP). With graphene additions, the mean average grain si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 22 publications
0
4
0
Order By: Relevance
“…WC-CO has become one of the most common materials for many applications requiring high temperature and high wear resistance like cutting tool in manufacturing industry [7]. It also includes machining of cast iron, various non-ferrous metals, etc.…”
Section: Wc-co-based Cutting Tool Materialsmentioning
confidence: 99%
See 1 more Smart Citation
“…WC-CO has become one of the most common materials for many applications requiring high temperature and high wear resistance like cutting tool in manufacturing industry [7]. It also includes machining of cast iron, various non-ferrous metals, etc.…”
Section: Wc-co-based Cutting Tool Materialsmentioning
confidence: 99%
“…Das et al [32] studied that graphene attracts particular interest due to its novel properties like high thermal conductivity, high mechanical strength and self-lubricating properties etc. Ali Nasser et al [7] used another methodology for stabilizing a predesigned Co gradient in the microstructure of nano-WC-Co thinning structure via graphene additions is presented. For this purpose, laminated specimens of green WC-Co functionally graded material, having three layers structured, with and without graphene additions in the intermediate layer were sintered at solid and liquid sintering temperatures of 1290 and 1400°C, respectively, using the hot isostatic pressing technique (HIP).…”
Section: Previous Work On Fabrication Of Tungsten Carbide-cobalt-base...mentioning
confidence: 99%
“…Yuan et al [3] demonstrated that the physical and tribology performances of WC-Co hardmetal are enhanced by adding graphene plated with Nickel. Nasser et al [4] designed a Co gradient structure in WC-Co hardmetal by manipulating graphene as a stabilizer to its Co gradient, resulting in the cemented carbide with an improved mechanical property. Chen et al [5] added graphene into the cemented carbide and the flexural strength was improved by ~50% accompanied by unabated hardness.…”
Section: Introductionmentioning
confidence: 99%
“…Taking into account the interest attracted by FGMs and ceramic/graphene composites, the aim of the present work is to take one step forward and merge both strategies, i.e., to develop continuous functionally graded Si 3 N 4 /graphene composites. Presently, there are scarce works devoted to graphene-based FGMs, most of them focused on polymeric matrices [10], although some studies related to WC ceramics can be found [11,12]. In these works, WC layers with distinct cobalt contents were stacked and liquid phase sintered.…”
Section: Introductionmentioning
confidence: 99%